Issues in localization of brain function: The case of lateralized frontal cortex in cognition, emotion, and psychopathology - Miller, Gregory A.; Crocker, Laura D.; Spielberg, Jeffrey M.; Infantolino, Zachary P.; Heller, Wendy (Frontiers in Integrative Neuroscience, 2013)
The appeal of simple, sweeping portraits of large-scale brain mechanisms relevant to psychological phenomena competes with a rich, complex research base. As a prominent example, two views of frontal brain organization have emphasized dichotomous lateralization as a function of either emotional valence (positive/negative) or approach/avoidance motivation. Compelling findings support each. The literature has struggled to choose between them for three decades, without success. Both views are proving untenable as comprehensive models. Recent evidence indicates that positive valence and approach motivation are associated with different areas in the left hemisphere. Evidence of other frontal lateralizations, involving distinctions among dimensions of depression and anxiety, make a dichotomous view even more problematic. Hemodynamic and electromagnetic neuroimaging studies suggest considerable functional differentiation, in specialization and activation, of subregions of frontal cortex, including their connectivity to each other and to other regions. Such findings contribute to a more nuanced understanding of functional localization that accommodates aspects of multiple theoretical perspectives.